Evaluating short and long term outcomes following pediatric Myringoplasty with Gelfoam graft for tympanic membrane perforation following ventilation tube insertion - Jin Soo Song; Gerard Corsten; Liane B. Johnson (Journal of Otolaryngology - Head and Neck Surgery)
Abstract Background Myringotomy with ventilation tube (VT) insertion to treat recurrent acute otitis media and chronic secretory otitis media has become one of the most common surgical procedures performed in children. Although contemporary literature has detailed the various patient and perioperative factors that affect successful pediatric myringoplasty, there is still limited evidence surrounding the increasing number of graft material options. In particular, gelfoam patching has arisen as a simple and efficient modality for perforation closure, but has a paucity of evidence particularly in pediatric cohorts. Our study aims to evaluate the clinical and audiometric outcomes following gelfoam myringoplasty for TMP following prolonged VT insertion in an urban pediatric population. Methods A retrospective review of pediatric patients who underwent myringoplasty between 2013 and 2018 following ventilation tube insertion. Patient demographics, comorbidities, and graft material were correlated with audiometric and clinical outcomes on follow up examination. Results One hundred twenty patients underwent myringoplasty, with 61 (50.8%) males with a mean age of 8.9 years old. 101 (84.2%) of patients eventually underwent successful tympanic membrane (TM) closure, with 93 (77.5%) demonstrating closure at initial follow up. In the gelfoam cohort, 77 (90.6%) of patients demonstrated successful TM closure at initial follow up. Overall mean time to closure was 5.6 (standard error (SE) 0.9) months. A multivariate Cox proportional hazards model demonstrated none of the covariates including graft material significantly affected TM closure. Mean change in air conduction threshold were comparable between graft materials. Conclusions Pediatric myringoplasty with gelfoam graft material is a safe and viable alternative with favorable short and long term clinical and audiometric outcomes.